Effect of Two Sudanese Cooking Methods on the Nutritional Value of Potato (Solanum tuberosum) Variety Draga (University of Khartoum Journal of Agricultural Sciences, 2023)
This work was carried out to assess the nutritive value of dragavariety of potato which was subjected to two cooking methods (boilingand frying). Proximate chemical analysis, minerals content, amino acidscontent and sensory evaluation were studied. Boiling resulted ininsignificant decrease in protein, ash, fat and starch and increase in fibreand a significant decrease in total carbohydrates, while frying increasedall tested components (protein, ash, fat, fibre, starch and totalcarbohydrates ). Generally, boiling and frying decreased significantly Na,K, P and Mg contents, while Fe was significantly increased. Ca wassignificantly increased by frying, while it was significantly decreased byboiling. The amino acids results showed that the two methods of cookingdestructed phenylalanine, methionine, tyrosine and lysine. However,arginine was destructed by boiling only. Tryptophan recorded completeabsence in all samples (raw, fried and boiled). Other amino acids (leucine,isoleucine, valine, histidine, aspartic acid, serine, glutamine and glycine)decreased by boiling and frying. Sensory evaluation revealed that therewas no significant difference between the two methods of cooking withregard to texture and colour. However, flavour, taste and overall qualityof fried potatoes were more acceptable than boiled ones.
Keywords: Potato; cooking style; nutritive value; draga variety